Differential expression of trypsin-3 and phosrestin ii genes in the main malaria vector, Anopheles darlingi, from the Brazilian Amazon Region - Ohse, K. C.; Matiolli, Cleverson Carlos; Scarpassa, Vera Margarete; Santos, V. S.; Tadei, Wanderli Pedro; Rafael, Míriam Silva (Genetics and Molecular Research, 2017)
Anopheles darlingi is the most anthropophilic mosquito related to Plasmodium infection of malaria, causing significant morbidity and mortality in South America. Pyrethroid chemical has been used to control mosquitos. We analyzed the expression of trypsin-3 and phosrestin II genes implicated to feeding and resistance to insecticides, immune response and sensory antenna mechanisms, respectively, of larvae and adult of A. darlingi, through quantitative reverse transcription polymerase chain reaction (qRT-PCR). We aimed to validate the similarity in nucleotide sequences of A. darlingi RNA sequencing libraries by in silico, and qRT- PCR, owing to their possible effects on the ability to spread disease. The expression of trypsin-3 and phosrestin II was higher in the first and second instar larvae as compared with that in adults. These differentially expressed trypsin-3 and phosrestin II genes do not provide us evidence that both genes participate in pyrethroid resistance. The signaling pathway involving both genes requires further study. Preliminary phylogenetic relationships and the accumulation of mutations analysis in both genes were also compared with trypsin and phosrestin sequences of 15 and 17 other anopheline species, respectively, to obtain a mutational rate of 0.02 on phylogenetic trees. Trypsin gene of A. darlingi and A. albimanus clustered into the same group and was distinct from the species of A. gambiae complex and other anopheline. For phosrestin II, A. darlingi was separated from the remaining species from Africa, Asia, and Europe. Although the groups showed low to moderate support, it is possible to infer that both genes may belong to two evolutionary groups: one presents in the anopheline species of New World and other in the anopheline species of Old World, and be useful for future studies. © 2017 The Authors.
Keywords: Pyrethroid; Adult; Amazonas; Anopheles; Anopheles Albimanus; Anopheles Darlingi; Anopheles Gambiae; Antenna (organ); Comparative Study; Computer Model; Controlled Study; Female; Gene Expression; Gene Mutation; Genetic Analysis; Immune Response; Insect Genetics; Insect Larva; Insecticide Resistance; Mosquito Vector; Mutation Rate; Nonhuman; Nucleotide Sequence; Phosrestin Ii Gene; Phylogenetic Tree; Phylogeny; Reverse Transcription Polymerase Chain Reaction; Rna Sequence; Signal Transduction; Trypsin 3 Gene